A novel hand exoskeleton with series elastic actuation for modulated torque transfer. (August 2019) - Marconi, Dario; Baldoni, Andrea; McKinney, Zach; Cempini, Marco; Crea, Simona; Vitiello, Nicola
Abstract: Among wearable robotic devices, hand exoskeletons present an important and persistent challenge due to the compact dimensions and kinematic complexity of the human hand. To address these challenges, this paper introduces HandeXos-Beta (HX-β), a novel index finger-thumb exoskeleton for hand rehabilitation. The HX-β system features an innovative kinematic architecture that allows independent actuation of thumb flexion/extension and circumduction (opposition), thus enabling a variety of naturalistic and functional grip configurations. Furthermore, HX-β features a novel series-elastic actuators (SEA) architecture that directly measures externally transferred torque in real-time, and thus enables both position- and torque-controlled modes of operation, allowing implementation of both robot-in-charge and user-in-charge exercise paradigms. Finally, HX-β's adjustable orthosis, passive degrees of freedom, and under-actuated control scheme allow for optimal comfort, robot-user joint alignment, and flexible actuation for users of various hand sizes. In addition to the mechatronic design and resulting functional capabilities of HX-β, this work presents a series of physical performance characterizations, including the position- and torque-control system performance, frequency response, end effector force, and output impedance. By each measure, the HX-β exhibited performance comparable or superior to previously reported hand exoskeletons, including position and torque step response times on the order of 0.3 s, −3 dB cut-off frequencies ranging from approximately 2.5 to 4 Hz, and fingertip output forces on the order of 4 N. During use by a healthy subject in torque-controlled transparent mode, the HX-β orthosis joints exhibited appropriately low output impedance, ranging from 0.42 to −0.042 Nm/rad at 1 Hz, over a range of functional grasps performed at real-life speeds. This combination of lab bench characterizations and functional evaluation provides a comprehensive verification of the design and performance of the HandeXos Beta exoskeleton, and its suitability for clinical application in hand rehabilitation.